1979
DOI: 10.1055/s-0028-1092793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Somatostatin on Bile-Induced Acute Hemorrhagic Pancreatitis in the Dog

Abstract: In 21 female Beagle dogs an experimental pancreatitis was induced by injection of bile into the pancreatic duct system. Beside controls, dogs received 62.5 micrograms/h cyclic somatostatin (SRIF) a continuous i.v. infusion starting with a bolus of 250 micrograms 15 minutes before or 2 hours after bile injection. Following blood parameters were determined: lipase, amylase, blood count, minerals, glucose, insulin, gastrin, secretin and CCK. Two controls died within 24 hours, the others were sacrificed after 48 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…[38]; (4) the reduction of splanchnic blood flow, since changes in microcirculation or hemodynamic properties can lead to possible cyto-and organoprotective as well as stimulatory effect of somatostatin and its analogue on the RES further deterioration in the disease [21][22][23]. However, other authors found octreotide to protect against postis- [28][29][30][31][32][33][34][35][36][37][38][39][40][41], and (5) the continuation of pancreatic enzyme synthesis after the induction of the disease [35]. chemic reperfusion injuries [24].…”
mentioning
confidence: 99%
“…[38]; (4) the reduction of splanchnic blood flow, since changes in microcirculation or hemodynamic properties can lead to possible cyto-and organoprotective as well as stimulatory effect of somatostatin and its analogue on the RES further deterioration in the disease [21][22][23]. However, other authors found octreotide to protect against postis- [28][29][30][31][32][33][34][35][36][37][38][39][40][41], and (5) the continuation of pancreatic enzyme synthesis after the induction of the disease [35]. chemic reperfusion injuries [24].…”
mentioning
confidence: 99%
“…Previous experimental data have shown that somatostatin could be used in acute pancreatitis, as it decreases the pancreatic damage and normalizes the blood enzyme levels [5,12,18]. One study was unable to show any influence of somatostatin on the development of the disease or the enzyme levels [ 13].…”
Section: Discussionmentioning
confidence: 85%
“…Some report that so matostatin is beneficial whilst others show no effect of the drug [5,12,13,18]. No con trolled clinical studies have been performed using somatostatin in acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Schwedes et al 26 induced acute pancreatitis in dogs and found considerable less inflammatory damage to the pancreas in animals treated with somatostatin. The "cytoprotective" effect of somatostatin was assumed to be the cause.…”
Section: Discussionmentioning
confidence: 99%